Model Komunikasi Interpersonal Orangtua terhadap Anak Autis - Syahrul Abidin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
Communication has an important role in human life, since childhood, humans have  communicated through the presence of parents. The role of parents greatly determines the process of developing communication in a child. But not all children are born in a normal state, including those who are blessed with a child with special needs such as autism. Even though every child has the potential in him, if he is not aware and cared for, it causes self-distrust in the child, a slow process of self-development, and some problems that are generally found in children with autistic disorders are in the social and communication aspects that are very lacking or slow . This paper focuses on discussing the model of interpersonal communication in developing the self potential of autistic disorder children. With document study methods that utilize various related research literature, as well as analytical techniques carried out by organizing and reducing data, then categorizing data, formulating to draw conclusions. The results of this paper indicate that many communication models must adapt to the characteristics of autistic disorders experienced by each child.